Effect of Essential Oils and Feed Enzymes on Performance and Nutrient Utilization in Broilers Fed a Corn/Soy-based Diet - Cao, P.H.; Li, F.D.; Li, Y.F.; Ru, Y.J.; Peron, A.; Schulze, H.; Bento, H. (International Journal of Poultry Science, 2010)
The objective of this study was to assess the effect of an encapsulated blend of Essential Oils (EOS) and a cocktail of various Enzymes (ES) including phytase and xylanase on the performance and nutrient utilization in broilers fed a corn/soy-based diet reduced in calcium, phosphorus and AME. Total 640 one day-old male chickens were allocated to 4 dietary treatments, following a 2 x 2 factorial design, 2 inclusion levels of EOS (0 or 100 g/t of feed) and 2 inclusion levels of ES (0 or 350 g/t of feed). The results indicated that there was no interaction in performance of broilers between EOS and ES. During the first three weeks, the mortality of broilers fed the diet containing EOS was lower (p<0.05) and the addition of EOS to the diet improved utilization of nitrogen and ileal digestibility of energy (p<0.05). In addition, EOS appeared to have affected gut microflora and the concentration of microbial nitrogen and Volatile Fatty Acids (VFA). On day 43, EOS supplementation increased the content of microbial nitrogen in ileum and caecum digesta and the concentration of acetate and butyrate in caecum (p<0.05), but it reduced the content of propionate in caecum. Supplementation of enzyme preparation at 350g/t to the basal diet improved the ileal digestibility of calcium and phosphorus as well as apparent metabolisability of energy and nitrogen (p<0.05). Supplementing enzyme preparation increased weight gain of broilers from 1 to 21 days. These results demonstrated that the addition of EOS and feed enzyme preparation in a corn/soy-based diet reduced in calcium, phosphorus and AME provided significant benefits in terms of nutrient utilization. The positive effect of EOS was more pronounced during the starter phase.